Camrelizumab plus albumin-bound paclitaxel and S-1 as first-line treatment for patients with human epidermal growth factor receptor 2-negative advanced gastric or gastroesophageal junction adenocarcinoma: a phase 2 trial - Wu, Chen; Li, Shuai; Hou, Xinfang (Frontiers in Immunology, 2026)
BackgroundCurrent first-line treatment options for human epidermal growth factor receptor 2 (HER2)-negative advanced gastric or gastroesophageal junction (G/GEJ) adenocarcinoma have limited efficacy. This study aimed to evaluate the efficacy and safety of camrelizumab plus albumin-bound paclitaxel and S-1 as first-line treatment for this population.MethodsIn this phase 2 trial (NCT04675866), patients received albumin-bound paclitaxel (125 mg/m2, days 1 and 8) and S-1 (40–60 mg per body surface area, twice daily on days 1-14) for 4–6 cycles of 21 days each. Camrelizumab (200 mg every 3 weeks) was concurrently initiated and continuously administered until disease progression, intolerable toxicity, or completion of 2-year treatment. The primary endpoint was objective response rate (ORR).ResultsBetween December 2020 and December 2024, 47 patients were enrolled. By the data cutoff date (January 6, 2025), the median follow-up duration was 16.7 months (range, 1.6-42.2 months). Among the 40 patients with evaluable efficacy, the ORR was 67.5% (95% CI: 52.3%-82.7%). The disease control rate was 95.0%. Median progression-free survival was 7.8 (95% CI: 6.2-9.4) months, and median overall survival was 23.8 (95% CI: 15.2-32.4) months. Grade 3–4 treatment-related adverse events(TRAEs) occurred in 18 patients (38.3%), with the most common being decreased neutrophil count (12 [25.5%]) and anemia (four [8.5%]).ConclusionThe combination of camrelizumab, albumin-bound paclitaxel, and S-1 as first-line treatment for patients with HER2-negative advanced G/GEJ adenocarcinoma showed promising efficacy and an acceptable safety profile. Randomized controlled clinical trials are required to further demonstrate its efficacy and optimal application scenario.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT04675866?term=Hou%20Xinfang&rank=1, identifier NCT04675866.